Indium Mineralization in the Volcanic Dome-Hosted Animas-Chocaya-Siete Suyos Polymetallic Deposit, Potosi, Bolivia - Torro, Lisard (2019)
A volcanic dome complex of Miocene age hosts the In-bearing animas-Chocaya-Siete Suyos district in SW Bolivia. Ore mineralization occurs as banded and massive infillings in sub-vertical, NE-SW striking veins. In this article, a detailed petrographic study is combined with in situ mineral geochemistry determinations in ore from the Arturo, Chorro and Diez veins in the Siete Suyos mine, the animas, Burton, Colorada, and Rosario veins in the animas mine and the Nueva vein in the Chocaya mine. A three-stage paragenetic sequence is roughly determined for all of them, and includes (1) an early low-sulfidation stage that is dominated by cassiterite, pyrrhotite, arsenopyrite, and high-Fe sphalerite (FeS > 21 mol. %); (2) a second intermediate-sulfidation stage dominated by pyrite + marcasite +/- intermediate product, sphalerite (FeS < 21 mol. %), stannite, and local famatinite; and, (3) a late intermediate-sulfidation stage dominated by galena and Ag-Pb-Sn sulfosalts. Electron-probe microanalyses reveal high indium enrichment in stage-2 sphalerite (up to 9.66 wt.% In) and stannite (up to 4.11 wt.% In), and a moderate enrichment in rare wurtzite (up to 1.61 wt.% In), stage-1 sphalerite (0.35 wt.% In), cassiterite (up to 0.25 wt.% In2O3), and ramdohrite (up to 0.24 wt.% In). Therefore, the main indium mineralization in the district can be associated to the second, intermediate-sulfidation stage, chiefly in those veins in which sphalerite and stannite are more abundant. Atomic concentrations of In and Cu in sphalerite yield a positive correlation at Cu/In = 1 that agrees with a (Cu+ + In3+) <-> 2Zn(2+) coupled substitution. The availability of Cu in the mineralizing fluids during the crystallization of sphalerite is, in consequence, essential for the incorporation of indium in its crystal lattice and would control the distribution of indium enrichment at different scales. The highest concentrations of indium in sphalerite, which is found in the Diez vein in the Siete Suyos mine, occur in crustiform bands of sphalerite with local chalcopyrite disease texture, which has not been observed in the other studied veins. In stannite, the atomic concentrations of In are negatively correlated with those of Cu and Sn at Cu + In = 2 and Sn + In = 1. Thus, atomic proportions and correlations suggest the contextualization of the main indium mineralization in the sphalerite-stannite-roquesite pseudoternary system.